SPE Annual Technical Conference and Exhibition 1996
DOI: 10.2118/36450-ms
|View full text |Cite
|
Sign up to set email alerts
|

Microseismic Monitoring of the B-Sand Hydraulic Fracture Experiment at the DOE/GRI Multi-Site Project

Abstract: Six hydraulic-fracture injections into a fluvial sandstone at a depth of 4500 ft were monitored with multi-level triaxial seismic receivers in two wells, resulting in maps of the growth and final geometry of each fracture based upon microseismic activity, These diagnostic images show that the hydraulic fractures are highly contained for smaller-volume KC1-water injections, but height growth is significant for the largervolume, higher-rate, higher-viscosity treatments. Fracture lengths for most injections are s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(24 citation statements)
references
References 0 publications
0
24
0
Order By: Relevance
“…Also, since microseisms do not necessarily occur on the hydraulic fracture itself (but can in fact be some distance to the side and/or ahead of fracture), it is difficult to determine completely accurate geometries of the fracture. According to Warpinski et al (1999) Other factors that can contribute to microseismic event location uncertainty are the distance from microseism to receiver and the azimuth of microseismic signals. From the same study done by Warpinski et al (1999), accuracy of the azimuth to the microseism is about ±5 o whereas uncertainty in the distance from the receiver to the microseism varies considerably depending upon the number of levels on which the S-wave arrival is accurately detected, but it is approximately on the order of ±50 ft.…”
Section: Downhole Methodology Vs Surface Methodologymentioning
confidence: 99%
“…Also, since microseisms do not necessarily occur on the hydraulic fracture itself (but can in fact be some distance to the side and/or ahead of fracture), it is difficult to determine completely accurate geometries of the fracture. According to Warpinski et al (1999) Other factors that can contribute to microseismic event location uncertainty are the distance from microseism to receiver and the azimuth of microseismic signals. From the same study done by Warpinski et al (1999), accuracy of the azimuth to the microseism is about ±5 o whereas uncertainty in the distance from the receiver to the microseism varies considerably depending upon the number of levels on which the S-wave arrival is accurately detected, but it is approximately on the order of ±50 ft.…”
Section: Downhole Methodology Vs Surface Methodologymentioning
confidence: 99%
“…According to Warpinski et al (1999) Other factors that can contribute to microseismic event location uncertainty are the distance from microseism to receiver and the azimuth of microseismic signals. From the same study done by Warpinski et al (1999), accuracy of the azimuth to the microseism is about ±5 o whereas uncertainty in the distance from the receiver to the microseism varies considerably depending upon the number of levels on which the S-wave arrival is accurately detected, but it is approximately on the order of ±50 ft. Given the uncertainties in microseism locations, the microseismic results in this research and other situations should be considered as an envelope that "surrounds" the fracture.…”
Section: Downhole Methodology Vs Surface Methodologymentioning
confidence: 99%
“…In the adjacent Rulison field, the combined impact of permeability, anisotropy, and depositional direction result in reservoir drainage taking a preferential east-west direction (Kuuskraa and Ammer, 2004). Studies of the stress field at the MWX site found the preferred fracture orientation in that area to be N74 to 80°W (azimuth of 106 to 111°) (Myal et al, 1989;Koepsell et al, 2003;Warpinski et al, 1996). Few fractures are found with orientations other than a general eastwest direction; outcrop studies indicate fracture strikes are within +/-25 degrees of east-west, implying only one fracture set (Nelson, 2003).…”
Section: Conceptual Flow Modelmentioning
confidence: 99%
“…Warpinski et al (1996) evaluated six hydrofrac operations in the B-sand fluvial sandstone (Williams Fork) at the MWX site, identifying a range in length from 53.3 to 106.7 m and a range in height of 12.2 to 41.1 m. They note that the length changes only slightly from tests of small-volume, low-viscosity fluids pumped at slow rates to larger volumes of high-viscosity fluids pumped at high rates, with the height being more affected. Another six hydrofrac operations were performed in the C-sand, resulting in fractures extending 121.9 to 152.4 m. However, diagnostics at an intersection well located at a distance of 87.5 m showed that the fractures were not conductive connections.…”
Section: Hydraulic Fracture Lengthmentioning
confidence: 99%